Influence of Genetics, Immunity and the Microbiome on the Prognosis of Inflammatory Bowel Disease (IBD Prognosis Study): the protocol for a Copenhagen IBD Inception Cohort Study - Johan Burisch; Lene Terslev; Mikkel Østergaard; Annette Bøjer Jensen; Frank Krieger Jensen; Flemming Bendtsen; Charlotte Wiell; Mohamed Attauabi; Klaus Theede; Viktoria Fana; Hartwig Roman Siebner; Henrik S Thomsen; et al. (BMJ Open)
Introduction Inflammatory bowel diseases (IBD), encompassing Crohn’s disease and ulcerative colitis, are chronic, inflammatory diseases of the gastrointestinal tract. We have initiated a Danish population-based inception cohort study aiming to investigate the underlying mechanisms for the heterogeneous course of IBD, including need for, and response to, treatment.Methods and analysis IBD Prognosis Study is a prospective, population-based inception cohort study of unselected, newly diagnosed adult, adolescent and paediatric patients with IBD within the uptake area of Hvidovre University Hospital and Herlev University Hospital, Denmark, which covers approximately 1 050 000 inhabitants (~20% of the Danish population). The diagnosis of IBD will be according to the Porto diagnostic criteria in paediatric and adolescent patients or the Copenhagen diagnostic criteria in adult patients. All patients will be followed prospectively with regular clinical examinations including ileocolonoscopies, MRI of the small intestine, validated patient-reported measures and objective examinations with intestinal ultrasound. In addition, intestinal biopsies from ileocolonoscopies, stool, rectal swabs, saliva samples, swabs of the oral cavity and blood samples will be collected systematically for the analysis of biomarkers, microbiome and genetic profiles. Environmental factors and quality of life will be assessed using questionnaires and, when available, automatic registration of purchase data. The occurrence and course of extraintestinal manifestations will be evaluated by rheumatologists, dermatologists and dentists, and assessed by MR cholangiopancreatography, MR of the spine and sacroiliac joints, ultrasonography of peripheral joints and entheses, clinical oral examination, as well as panoramic radiograph of the jaws. Fibroscans and dual-energy X-ray absorptiometry scans will be performed to monitor occurrence and course of chronic liver diseases, osteopenia and osteoporosis.Ethics and dissemination This study has been approved by Ethics Committee of the Capital Region of Denmark (approval number: H-20065831). Study results will be disseminated through publication in international scientific journals and presentation at (inter)national conferences.